2022
DOI: 10.1021/acsnano.2c06890
|View full text |Cite
|
Sign up to set email alerts
|

Optimized NiFe-Based Coordination Polymer Catalysts: Sulfur-Tuning and Operando Monitoring of Water Oxidation

Abstract: In-depth insights into the structure–activity relationships and complex reaction mechanisms of oxygen evolution reaction (OER) electrocatalysts are indispensable to efficiently generate clean hydrogen through water electrolysis. We introduce a convenient and effective sulfur heteroatom tuning strategy to optimize the performance of active Ni and Fe centers embedded into coordination polymer (CP) catalysts. Operando monitoring then provided the mechanistic understanding as to how exactly our facile sulfur engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…To obtain in-depth insight into the role of sulfur heteroatom incorporation in the OER kinetics, our group performed operando XAS experiments with newly designed NiFe-based coordination polymer-based OER catalysts that were doped with S atoms (S-R-NiFe-CPs). 647 Our results indicated that engineering of sulfur heteroatom incorporation promotes the generation of catalytically active moieties of high-valent S−Ni IV In addition to sulfur, chlorine incorporation has also been reported to trigger the restructuring of various materials. In a representative example, by means of operando XAS characterization and DFT calculations, Song et al probed the structural optimization of a new class of Co 2 (OH) 3 Cl OER precatalysts.…”
Section: ) Leaves the Following Question Open: Do The Oxidized Anioni...mentioning
confidence: 58%
See 2 more Smart Citations
“…To obtain in-depth insight into the role of sulfur heteroatom incorporation in the OER kinetics, our group performed operando XAS experiments with newly designed NiFe-based coordination polymer-based OER catalysts that were doped with S atoms (S-R-NiFe-CPs). 647 Our results indicated that engineering of sulfur heteroatom incorporation promotes the generation of catalytically active moieties of high-valent S−Ni IV In addition to sulfur, chlorine incorporation has also been reported to trigger the restructuring of various materials. In a representative example, by means of operando XAS characterization and DFT calculations, Song et al probed the structural optimization of a new class of Co 2 (OH) 3 Cl OER precatalysts.…”
Section: ) Leaves the Following Question Open: Do The Oxidized Anioni...mentioning
confidence: 58%
“…For example, a recent operando XAS study showed that the thickness of the prepared IrO 2 OER electrodes and the underlying catalyst loss through dissolution or delamination can drastically influence the apparent oxidation state of Ir during the OER . To avoid such artifacts, a catalyst mass loading range of 1–2 mg cm –2 (such as from our practical experience of operando XAS on CoP and NiFe-CPs) and a low X-ray flux (≤0.5 × 10 12 photons mm –2 s –1 ) are recommended for conducting a proper in situ / operando XAS experiment. Another important aspect to consider during in situ / operando X-ray or microscopy experiments is that the interaction between the electrolyte and beam might produce a significant number of radicals due to water radiolysis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4d–g). 82 Greta R. Patzke et al 83 reported a related study on sulfide reduction of the NiFe coordination polymer ( S-R -NiFe-CP). The Ni K-edge XANES spectra of S-R -NiFe CPs at applied potentials between 0.8 and 1.45 V vs. RHE were recorded.…”
Section: High-valence Metal Site Constructionmentioning
confidence: 99%
“…The high-quality energy conversion effect and efficiency of energy utilization pursued by electrocatalysis are regarded as one of the important ways to solve the energy crisis. With the rapid development of electrochemical reaction (hydrogen generation, CO 2 and N 2 reduction), oxygen evolution reaction (OER), which provides electrons and protons for them, cannot be ignored. Meanwhile, the reaction environment of the OER application is also more complex, which induces greater challenges for the corresponding research mechanism and catalyst design. …”
Section: Introductionmentioning
confidence: 99%